The toxicity and efficacy of concomitant chemoradiotherapy in patients aged 70 years and older with oropharyngeal carcinoma in the intensity‐modulated radiotherapy era. Issue 8 (16th December 2016) - Zumsteg, Zachary S.; Lok, Benjamin H.; Ho, Allen S.; Drill, Esther; Zhang, Zhigang; Riaz, Nadeem; Shiao, Stephen L.; Ma, Jennifer; McBride, Sean M.; Tsai, C. Jillian; Baxi, Shrujal S.; Sherman, Eric J.; et al.
Abstract : BACKGROUND: Despite controversy surrounding its benefit, the use of concomitant chemoradiotherapy (CCRT) in patients with oropharyngeal squamous cell carcinoma (OPSCC) who are aged > 70 years is increasing. However, to the authors' knowledge, few studies to date have compared the outcomes of different systemic treatments in this population. METHODS: Records from 74 patients aged ≥ 70 years with stage III to stage IVB OPSCC who were undergoing CCRT from 2002 to 2013 at a single institution were reviewed. Patients were stratified according to the systemic therapy received, including cisplatin, carboplatin with either 5‐fluorouracil or paclitaxel (CARB), or cetuximab to compare oncologic outcome and toxicity. RESULTS: The median follow‐up was 36 months. The median age of the patients was 75.3 years (range, 70‐91 years), with significantly older patients receiving cetuximab ( P  = .03). A total of 28, 20, and 26 patients, respectively, received CCRT with cisplatin, CARB, and cetuximab. RT interruptions of > 1 day were needed in 4% of patients receiving cisplatin, 20% of patients receiving CARB, and 15% of patients receiving cetuximab ( P  = .19). Unplanned hospitalizations during CCRT occurred in 25%, 55%, and 58%, respectively, of patients receiving cisplatin, CARB, and cetuximab ( P  = .03). There were 2 treatment‐related deaths, both of which occurred among the patients who were treated with cetuximab. At 5 years, locoregional control was achieved in 100%, 88%, and 60% ( P <.001), respectively, and the overall survival rate was 87%, 61%, and 47% ( P  = .03), respectively, among patients treated with cisplatin, CARB, and cetuximab. CONCLUSIONS: Toxicity from CCRT remains a challenge for older adults with OPSCC. Herein, the authors found no evidence that this toxicity was mitigated by treatment with cetuximab. Nevertheless, a subset of patients aged ≥70 years appear to tolerate cisplatin‐based treatment with acceptable toxicity and excellent outcomes. Further identification of this patient subgroup is crucial to optimize therapy for older patients with OPSCC. Cancer 2017;123:1345–1353. © 2016 American Cancer Society . Abstract : In the current study, a subgroup of patients aged ≥70 years with oropharyngeal squamous cell carcinoma who were deemed fit for cisplatin‐based chemoradiation have excellent outcomes, with no locoregional disease recurrences and acceptable toxicity, whereas those patients deemed unfit for cisplatin therapy and receiving cetuximab have relatively high acute toxicity and inferior locoregional control. These results suggest that the older population of patients with oropharyngeal carcinoma is extraordinarily heterogeneous, and tools for improved patient stratification are desperately needed.